Intensity of growth of pigs in the growing facility with the addition of the bio-logical supplement “MikoStop” to the diet - H. Ohorodnichuk; V. Zagamula (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Fodder sorbents are used to feed agricultural animals to improve consumption, increase feed use efficiency, and improve product quality. Our experimental studies aimed to study the effect of the complex biological sorbent “MikoStop” on the intensity of growth of crossbred piglets during rearing and establish the optimal dose of the additive. The article presents the research results on the effect of feeding the complex biological sorbent “MikoStop” on the intensity of growth of pigs in growing farms. The scientific and economic experiment was carried out on four similar groups of pigs on the rearing farm, 14 heads in each, obtained from crossing sows of the large white breed with boars of the landrace breed. The control group of pigs consumed the main ration – full-ration combined feed TM “Tsekhavit” during the equalization and main periods. In addition to the main diet, the experimental groups were fed various doses of the complex biological sorbent “MikoStop.” The comparative and main experimental periods were 10 and 45 days, respectively. The researched additive “MikoStop” is produced SE “Enzym,” Ukraine. “MikoStop” is a complex biological sorbent of feed toxins with probiotic, antiviral, hepatoprotective, and immunoprotective properties. Ingredients: activated particular yeast cell walls, mannan-oligosaccharides, mineral carrier, and probiotic culture. It was established that feeding pigs with the complex biological sorbent “MikoStop” at a dose of 0.5 kg/1 t of compound feed increases live weight and absolute growth by 1.39 kg or 4.3 %, and by 1.37 kilograms or 5.4 %, respectively % kg, and increases average daily gains by 30.45 g or by 5.7 % compared to control indicators. At the same time, under the influence of the feed additive, the growth energy of piglets increased by 2.57 % compared to animals of the control group. Using the complex biological sorbent “MikoStop” allows you to reduce the cost of feed per 1 kg of growing pigs and increase the payment of feed by growth.